Metabolomics Analysis Reveals Dynamic Accumulation of Sugar and Acid during Stem Development of Brassica juncea - Fangjie Xie; Zhengying Xuan; Wanqin Chen; Jiageng Du; Yalin Wang; Entong Huo; Ling Guo; Mengyao Li (Agronomy, 2022)
The composition and content of sugar and acid are important indicators of organ development and the quality of horticultural products. B. juncea is an important vegetable in the cruciferous family, with a swollen fleshy stem as the edible organ. Elucidating the characteristics of sugar and acid accumulation during stem expansion of stem mustard and its regulatory mechanism could enhance stem quality. In this study, physiological indicators such as dry matter content, sugar–acid content and related enzyme activities were measured in eight stages of the tumorous stem. The results showed that the sugar and sucrose contents initially increased and then decreased during stem development: Sucrose exhibited a positive correlation with sucrose synthase and sucrose phosphate synthase, while acid content was highly positively correlated with malate dehydrogenase. Further analysis of the dynamic patterns of sugar and acid metabolite contents using metabolomics showed that 1097 metabolites were detected, including 229 organic acids and derivatives, 109 lipids, and other metabolites. Metabolic pathway enrichment analysis showed that metabolites were significantly enriched in organic acids, amino acids, glycolysis/gluconeogenesis, starch, and sucrose metabolism. Analysis of the sugar pathway and the tricarboxylic acid cycle revealed obvious differences in the content and type of metabolites, with most upregulated metabolites in S3 and S4. The expression patterns of enzyme genes associated with the biosynthesis and accumulation of sugar and acid metabolites were found based on differentially expressed genes at different developmental stages, and gene expression levels were verified by qPCR, which showed that the expression patterns of enzyme genes associated with this pathway were highly consistent with the metabolite accumulation. These results suggest that amino acids, sugars, and acids play a critical role in regulating the development of tumorous stems. Results of the present study offer a theoretical basis to improving the quality of mustard by using a metabolomics approach to determine the dynamics of metabolites and related regulatory enzymes during development and the correlation between these levels, which provides novel insights into the potential mechanisms underlying sugar and acid metabolism.